2006
DOI: 10.1002/nur.20125
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, social alienation, and depressed mood in midlife women from the former Soviet Union

Abstract: Level of acculturation has been linked to depressed mood in studies across culturally diverse immigrant groups. The purpose of this study was to determine the effects of acculturation, social alienation, personal and family stress, and demographic characteristics on depressed mood in midlife immigrant women from the former Soviet Union. Structural equation modeling showed that higher acculturation scores, measured by English language and American behavior, were indirectly related to lower scores for depressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 46 publications
4
61
0
4
Order By: Relevance
“…A study of South Asian immigrants in America reveals that acculturation and racial identity accounted for variance in depressed or anxious mood [22]. Similarly, a study of immigrants from the former Soviet Union in the US shows that higher acculturation levels were associated with lower personal stress and anxiety [23], anda research finding of Turkish immigrants in the Netherlands discloses that participation in Dutch culture was associated with a decrease of depressive and anxious mood [24]. …”
Section: Total Sampled Immigrantsmentioning
confidence: 99%
“…A study of South Asian immigrants in America reveals that acculturation and racial identity accounted for variance in depressed or anxious mood [22]. Similarly, a study of immigrants from the former Soviet Union in the US shows that higher acculturation levels were associated with lower personal stress and anxiety [23], anda research finding of Turkish immigrants in the Netherlands discloses that participation in Dutch culture was associated with a decrease of depressive and anxious mood [24]. …”
Section: Total Sampled Immigrantsmentioning
confidence: 99%
“…Modern conceptualizations of acculturation emphasize cultural learning and behavioral adaptation, and incorporate cognitive and emotional components of accessing, understanding, and adopting specific aspects and characteristics of a majority culture while also retaining characteristics of one's ethnocultural heritage (Miller, Sorokin, Wang, Feetham, Choi, & Wilbur, 2006). Thus, acculturation is best conceptualized as a dynamic, multifaceted construct influenced by contextual and internal factors (Miller et al, 2006;Zane & Mak, 2003).…”
Section: Acculturationmentioning
confidence: 99%
“…Modern conceptualizations of acculturation emphasize cultural learning and behavioral adaptation, and incorporate cognitive and emotional components of accessing, understanding, and adopting specific aspects and characteristics of a majority culture while also retaining characteristics of one's ethnocultural heritage (Miller, Sorokin, Wang, Feetham, Choi, & Wilbur, 2006). Thus, acculturation is best conceptualized as a dynamic, multifaceted construct influenced by contextual and internal factors (Miller et al, 2006;Zane & Mak, 2003). Berry's (2003) model of acculturation argues that acculturating individuals exhibit specific acculturative styles, which corresponds to the level of adaption to the culture in which one is embedded, as well as the involvement in behaviors and practices associated with their heritage culture.…”
Section: Acculturationmentioning
confidence: 99%
“…Findings also indicated that greater social alienation increases the vulnerability to depression in a sample of 226 midlife women from the former Soviet Union (Miller et al, 2006). Prior to subject identification and recruitment, approval was obtained from the University Institutional Review Board (IRB) and from the faculty of nursing to conduct the parent study from which this secondary analysis was obtained.…”
Section: Alienation and Depressionmentioning
confidence: 99%